ANTIBACTERIAL ACTIVITY OF ETHANOL EXTRACTS AND n-hexane OF (Centella asiatica (L.) Urb.) AGAINST THE Pseudomonas aeruginosa AND Bacillus subtilis - Fikayuniar, Lia; Hari Kusumawati, Anggun; Abriyani, Ermi; Ridwanuloh, Dadan; Ichsani, Sakina (International Journal of Psychosocial Rehabilitation, 2020)
Centella asiatica (L.) Urb.) Is a plant that has antifungal and antibacterial bioactive compounds. Centella asiatica (L.) Urb.) Is one of the main herbs for treating skin problems, healing wounds and being an antibacterial and antiviral agent. Centella asiatica (L.) Urb.) Leaf samples taken from the manoko bandung plantation were extracted using 96% ethanol and n-hexane, the extract was thickened and a thick extract was obtained which was then tested for its antibacterial activity. Antibacterial activity test uses the paper disk diffusion method and tested against the bacteria Pseudomonas aeruginosa and Bacillus subtilis. The extract concentrations used were 7.5%, 10%, 12.5% and 15%. The positive control used is tetracycline while the negative control used is DMSO. The results showed that ethanol extract was effective in inhibiting the growth of Bacillus subtilis bacteria with an average inhibition zone of 10.41 mm and included in the strong category. As for n-hexane, it is effective in inhibiting the growth of Bacillus subtilis bacteria with inhibition zones 23.19 and categorized as very strong inhibition. The ethanol and n-hexane extracts of Centella asiatica (L.) Urb.) Leaves are effective in inhibiting bacteria from the gram positives group because gram positives have a simpler cell wall with a relatively large number of peptidoglycan.